Análisis de la relación genotipo ambiente con seis variedades de café (coffea spp..) en la granja experimental santa inés - Armijos Villavicencio, Adriana Estefania (Machala : Universidad Técnica de Machala, 2020)
The present research was carried out at the Technical University of Machala, Faculty of Agricultural Sciences in the Experimental Area of the Santa Inés Farm located at km 5.5 of the Machala - Pasaje road. Six varieties of coffee donated by the Municipality of Zaruma from the coffee seedbed were evaluated. The objective of this research was to determine the most suitable genotypes according to soil and climate conditions for the establishment of production plots in the experimental area of the Santa Inés Farm. Twenty morphoagronomic descriptors were taken. Repeated plots were made with thirty-five plants per genotype having a total of six hundred fifty-eight coffee plants, shade was implemented using musaceous plants. The morphoagronomic descriptors studied were the habit of the plant, plant height, trunk diameter, plant radius, number of branches per plant, number of leaves per plant, branching habit, shape of the stipulum, length of the stipulum edges, color of the young leaf, leaf length, leaf width, leaf shape, shape of the leaf apex, length of the leaf petiole, color of the leaf petiole, design of the ribbing, branch length, branch distance, leaf distance. With the data obtained from the research on the morphoagronomic characterization of the different varieties of coffee, a Diagram of marginal means was made to identify which variety was the best adapted to the edaphoclimatic conditions of the zone, being the Geisha variety the one that presented the best behavior in relation to the other varieties. The descriptors that presented a level of significance lower than 0.05 were the HP (plant height), RP (plant radius), LH (leaf length), LR (branch length). In addition, a Dendrogram based on similarity distance was carried out, which resulted in three well-defined groups that showed the phenotypic diversity among the six varieties of coffee. Group one was made up of four varieties: Conilon, Sarchimor, Criolla robusta 1 and Geronimo, which showed similarities among them, unlike groups two and three, which were made up of a single variety called Robusta Criolla 2 and Geisha, the first group among them the most discriminating descriptors ZLR (branch length), ZDR (branch distance), ZHP (plant height), ZNR (branch number), ZDT (trunk diameter), ZRP (plant radius) which are the ones that establish greater viability in the six coffee varieties, followed by the second group of intermediates that may or may not be discriminant ZDH (leaf distance), ZLH (leaf length), ZAH (leaf width), ZDB (shoot distance) and the third group of non-discriminant descriptors ZNH (number of leaves), ZLPF (leaf petiole length), ZLA (edge length). In recommendation these materials are of great value for the future for projects in plant breeding because of their agronomic characteristics for obtaining new cultivars that will help the farmer to improve Ecuador's production in the coffee sector.
El presente trabajo de investigación se desarrolló en la Universidad Técnica de Machala, Facultad de Ciencias Agropecuarias en el área Experimental de la Granja Santa Inés ubicada en el km 5.5 de la vía Machala – Pasaje, fueron evaluadas seis variedades de café donadas por el Municipio de Zaruma del semillero de café. El objetivo de esta investigación fue determinar los genotipos más idóneos en función de las condiciones edafoclimáticas para el establecimiento de parcelas de producción en el área experimental de la Granja Santa Inés, se tomaron veinte descriptores morfo agronómicos. Se realizaron parcelas repetidas con treinta y cinco plantas por genotipo teniendo un total de seiscientos cincuenta y ocho plantas de café, se implementó sombra utilizando musáceas. Los descriptores morfo agronómicos estudiados fueron: el hábito de la planta, altura de la planta, diámetro del tronco, radio de la planta, número de ramas por planta, número de hojas por planta, hábito de la ramificación, forma de la estipula, longitud de las aristas de la estipula, color de la hoja joven, longitud de la hoja, ancho de la hoja, forma de la hoja, forma del ápice de la hoja, longitud del peciolo foliar, color del peciolo foliar, diseño de la nervadura, longitud de la rama, distancia de rama, distancia de hojas. Con los datos obtenidos de la investigación sobre la caracterización morfo agronómicos de las diferentes variedades de café se realizó un Diagrama de medias marginales para identificar qué variedad fue la que mejor se adaptó a las condiciones edafoclimáticas de la zona, siendo la variedad Geisha la que presentó el mejor comportamiento en relación a las otras variedades. Los descriptores que presentaron un nivel de significancia menor a 0.05 fueron los HP (Altura de la planta), RP (Radio de la planta), LH (Longitud de la hoja), LR (Longitud de la rama). Además se realizó un Dendrograma basada en distancia de similitud donde resultaron tres grupos bien definidos el cual se evidenció la diversidad fenotípica entre las seis variedades de café, el grupo uno formado por cuatro variedades Conilon, Sarchimor, Criolla robusta 1 y Gerónimo presentando similitudes entre ellas a diferencia del grupo dos y tres conformados por una sola variedad denominadas Robusta Criolla 2 y Geisha, también se realizó un análisis de componentes principales (PCA), que permitió establecer los descriptores más discriminantes agrupándolos en grupos, el primero grupo entre ellos los descriptores más discriminantes ZLR (Longitud de rama), ZDR (Distancia de rama), ZHP (altura de la planta), ZNR (número de rama), ZDT (diámetro del tronco), ZRP (Radio de la planta) que son los que establecen mayor viabilidad en las seis variedades de café, seguido por el segundo grupo de intermedios que pueden ser o no ser discriminantes ZDH (distancia de hoja), ZLH (longitud de la hoja), ZAH (ancho de la hoja), ZDB (distancia de brotes) y el tercer grupo de los descriptores no discriminantes ZNH (número de hojas), ZLPF (longitud del peciolo foliar), ZLA (longitud de la arista). En recomendación estos materiales son de gran valor para el futuro para proyectos en fitomejoramiento por sus características agronómicas para la obtención de nuevos cultivares que ayudarán al agricultor a mejorar la producción del Ecuador en el sector cafetalero.
Keywords: ANÁLISIS; RELACIÓN; GENOTIPO; CAFÉ